Identifying Active Hot-Issue Communicators and Subgroup Identifiers: Examining the Situational Theory of Problem Solving. (March 2017) - Chen, Yi-Ru Regina; Hung-Baesecke, Chun-Ju Flora; Kim, Jeong-Nam
This study used the situational theory of problem solving (STOPS) to investigate communication behaviors of publics formed around an intensively publicized policy issue. Results of surveying 748 participants online support the utility of STOPS to segment the hot-issue public with active communication from the general population in a Chinese context. However, problem recognition does not significantly correlate with situational motivation. Between the examined cross-situational variables, party identity serves as a better identifier of the hot-issue public's subgroups than trust in the government. Theoretical implications for hot-issue publics and STOPS and practical implications for effective communication to the hot issue are discussed.